SINONIM NOMINA BAHASA MELAYU MANADO - Pantouw, Lidya Anita Afny (Universitas Sam Ratulangi, 2018)
This research focuses on the problems of synonymy of the nouns in Malay Manado language. The objectives of the research are to describe the distinctive features among synonymous nouns in Malay Manado language. This research is descriptive research, of the type of the text analysis (content analysis), using the primary data (written) taken from Kamus Bahasa Malay Manado and the secondary data from the informants. The data were collected using the documentary method, listen and note taking method, and elicitation method. The analysis process was done using the orthographic similarity method because the standards are in the written form. Then, the similarity technique used was connect and compare equate technique (teknik hubung banding menyamakan (HBS)); and connect and compare distinguish technique (teknik hubung banding membedakan (HBB)). The analyses revealed the following: most Malay Manado nouns have near synonyms; there are general semantic features among the synonymous pairs of nouns; the pairs of the synonymous nouns are near synonyms because there are some distinguishing features (there are differences in aesthetic sense among the speakers, there are differences in the medium of sentences which use synonymous nouns, there are uncommon usage of nouns considered synonymous, and there are influences of dialects in the use of synonymous nouns). The use of synonymous nouns in the communication (both in spoken and written texts, both formal and informal usage), requires the accuracy on the part of the speakers due to the fact that there are distinguishing features in each of the synonymous pairs. This would avoid the obscurity and misunderstanding in receiving the information.Keywords: synonymous nouns, near synonym, distinguishing components of meaning, connect and compare equate technique, connect and compare distinguish technique